“No masses without Muslims’ approval” The Crisis of Building and Restoring Churches in Egypt: Three Case Studies from El-Minya Governorate - Shaltout, Sara (AUC Knowledge Fountain, 2022)
This thesis examined the crisis of building and renovating churches in Egypt in the light of the Church-state relation. I focused on three case studies in the El-Minya governorate that includes the largest Christian concentration in the Middle East to shed light on the existing difficulties that face Christians there regarding building a house of worship. The first case study, "church No 1", was demolished due to political conflict between Islamists and the state after the Rabaa massacre in 2013. In comparison, church No 2 asserts that Muslims' approval is a prerequisite for Christians' prayers. In addition to church No 3, a moving church, the Christians could not build a settled one because of Muslims' opposing. Both cases confirm that the law 80/2016 of building and renovating churches is being violated or needs to be amended. In this thesis, I argue that building and renovating churches in Egypt is a crisis that challenges the Egyptian state from one hand and reflects the current church-state relation from another